Colour vision in marine organisms. (October 2015) - Marshall, Justin; Carleton, Karen L; Cronin, Thomas
Highlights: Most marine animals possess no or relatively simple colour vision, for example, monochromacy or dichromacy. The 12 spectral channel unconventional colour vision of stomatopods is an exception in the ocean. Colour vision diversity is greater in the ocean than on land due to extremes in photic habitat and colour behaviours. Sequencing may reveal more opsins than functional at any one time, but which provide substrate for rapid adaptation. There is an as yet unexplained diversity of colour vision and colour signals among teleost fish possibly resulting from neutral drift. Abstract : Colour vision in the marine environment is on average simpler than in terrestrial environments with simple or no colour vision through monochromacy or dichromacy. Monochromacy is found in marine mammals and elasmobranchs, including whales and sharks, but not some rays. Conversely, there is also a greater diversity of colour vision in the ocean than on land, examples being the polyspectral stomatopods and the many colour vision solutions found among reef fish. Recent advances in sequencing reveal more opsin (visual pigment) types than functionally useful at any one time. This diversity arises through opsin duplication and conversion. Such mechanisms allow pick-and-mix adaptation that tunes colour vision on a variety of very short non-evolutionary timescales. At least some of the diversity in marine colour vision is best explained as unconventional colour vision or as neutral drift.